The identification of influential spreaders and communities in complex networks - Sun, Hong-Liang (2018)
This thesis deals with two main research topics in the field of complex network science, including the identification of influential spreaders from the view of nodes and their community discovery from the view of groups of nodes. It aims at understanding the mechanism of a small number of initial nodes known as information sources leading to wide information propagation in social networks. The discovery of communities that these spreaders belong to is another key factor of identifying influential spreaders. Heterogeneous community detection is a vital step towards the understanding of network topological structures and propagation dynamics. These two questions are not isolated but have certain relationship in our study. In this thesis, we have made the following novel contributions.